What have we learned from ICON1 and ACTION?. (1st October 2003) - Colombo, N.; Pecorelli, S.
Abstract : Still, 20–30% of women with early-stage ovarian cancer eventually die from their disease. Adequate treatment for this subset of patients has not yet been identified, the greatest dispute being about the role of adjuvant therapy after surgical staging. No randomized trial has reliably demonstrated a survival advantage for one of the many approaches over another or over careful observation without immediate further adjuvant therapy. A combined analysis of two parallel randomized clinical trials in early ovarian cancer, ICON 1 and ACTION, comparing platinum-containing adjuvant chemotherapy to observation following surgery was performed, with survival as primary end point and time to recurrence as a secondary one. A total of 924 patients were randomized. With over 4 years median follow up for survivors, the hazard ratio for recurrence-free survival is 0.64 (95% CI, 0.50–0.82; P = 0.001) in favor of adjuvant chemotherapy, with an absolute difference of 11%. For overall survival, the hazard ratio is 0.67 (95% CI, 0.50–0.90; P = 0.008) in favor of adjuvant chemotherapy. These results translate into an absolute difference of 8% in the adjuvant chemotherapy group and indicate that adjuvant platinum-containing chemotherapy improves the survival and disease-free survival. Sub-group analysis demonstrated in the ACTION trial that completeness of surgical staging was an independent factor for prognosis, both for progression-free and for overall survival (along with histological type and tumor grade), while in suboptimally staged patients, adjuvant chemotherapy did improve the outcome.